Moving wooden crates. - Gordon, John C. (photographer):::Creator::::::::::::
Storage room or warehouse. A man moves a pallet of wooden crates on a dolly. Stamped on some crates: "Geo. Reid, San Jose;" "Geo. Frank Co., San Jose;" "H.B. Kooser, Almaden."